Phytochemical profiling and antidiabetic evaluation of Peperomia pellucida as a potential alpha glucosidase inhibitor - SHOLIHATIL HIDAYATI; AYU TRI AGUSTIN; ENI KARTIKA SARI; SHINTA MAYA SARI; RIAN ANGGIA DESTIAWAN; WARDA ATIKA SILVANA (Society for Indonesian Biodiversity, 2023)
Abstract. Hidayati S, Agustin AT, Sari EK, Sari SM, Destiawan RA, Silvana WA. 2023. Phytochemical profiling and antidiabetic evaluation of Peperomia pellucida as a potential alpha glucosidase inhibitor. Biodiversitas 24: 5972-5978. One strategy in post-prandial hyperglycemic control can be done by inhibiting the digestion of dietary carbohydrates through the inhibition of alpha glucosidase enzymes. This study was conducted to determine the antidiabetic activity of Peperomia pellucida in inhibiting the alpha glucosidase. An inhibitory activity analysis test was carried out on alpha glucosidase in vitro and in silico using alpha glucosidase. Molecular docking between receptors and ligands was performed using Hex 8.0 software. The setting column is set in Shape+Electro+DARS mode. The results showed ethanol extract and ethyl acetate fraction in vitro showed the ability to inhibit the activity of alpha glucosidase enzyme with C50 values of 13.43 mg/mL and 9.73 mg/mL respectively with IC50 positive control acarbose values of 8.11 mg/mL. The results of in silico analysis showed that the Patuloside A component was able to bind to the binding site of alpha glucosidase and gave the smallest binding energy value with a value of -321.4 kcal/mol compared to isovitexin, isoswertisin, pellucidatin, and caryatin-7-O-?-rhamnoside compounds. P. pellucida has the potential to be developed as an antidiabetic agent that has activity in inhibiting the work of the enzyme alpha glucosidase so that it can reduce blood glucose levels.